Determining the Ability of Senior Dental Students to Detect Interproximal Caries Using Different Radiographic Techniques - Muzan Abdalla; Saadika B. Khan (Hindawi Limited, 2024)
Clinical Significance: Teachings and availability of diverse radiological diagnostic techniques ensured a reasonable level of understanding and use of the diagnostic caries risk assessment methodologies as required in restorative treatment planning.